Hard-of-Hearing (HH) Students’ Perceptions of Multimodal EFL Learning - Nur Arifah Drajati; Bunga Ikasari; Rizka Junhita (Institut Agama Islam Negeri (IAIN) Kendari, 2021)
Learners with hearing loss tend to learn visually. It attracted a teacher of hard-of-hearing (HH) students in a special needs school to implement multimodality that integrated all verbal and visual semiotic modes and used ICT in her English classroom. The study aims to explore the students’ perceptions of multimodal English learning. The interview of the two females and one male participant individually. In addition to the data gained from the interview, students' diaries were also analyzed based on themes that emerged from the codes and categories. The data were triangulated by checking the interviews with the diaries and confirming with the teacher and the students' parents. The findings of the study revealed both positive and negative perceptions emerged. The students perceived ICT-based multimodal learning positively to help them learn new vocabularies and understand a story quickly, increase their motivation to learn, improve their engagement, and make them able to learn autonomously. Meanwhile, they perceived the EFL learning negatively so that it took much time to learn all of the materials. Also, the students felt unconfident in performing activities. Therefore, it is recommended for HH teachers to provide more significant assistance, time, and patience to successfully support students in learning English.